2014
DOI: 10.1177/0954411914522024
|View full text |Cite
|
Sign up to set email alerts
|

Heterotopic ossification in cervical total disk replacement: A finite element analysis

Abstract: Heterotopic ossification is one of the possible complications following cervical total disk replacement. Although there are numerous hypotheses regarding the etiology of heterotopic ossification, the main causes of heterotopic ossification remain unknown. In this study, we hypothesize that heterotopic ossification formation is related to external loading in the cervical vertebrae after total disk replacement. A two-dimensional finite element model of a cervical vertebra treated by total disk replacement in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 33 publications
0
14
1
Order By: Relevance
“…The biomechanical advantage of CDA has been demonstrated previously that it can maintain segmental range of motion and cervical kinematics, theoretically reducing or avoiding adjacent segment degeneration [ 12 16 ]. However, CDA has its own potential disadvantages, such as higher incidence of heterotopic ossification [ 17 20 ] and implant migration or subsidence [ 21 24 ]. Many investigators have reported RCTs comparing CDA with ACDF for the treatment of symptomatic cervical disc disease [ 25 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…The biomechanical advantage of CDA has been demonstrated previously that it can maintain segmental range of motion and cervical kinematics, theoretically reducing or avoiding adjacent segment degeneration [ 12 16 ]. However, CDA has its own potential disadvantages, such as higher incidence of heterotopic ossification [ 17 20 ] and implant migration or subsidence [ 21 24 ]. Many investigators have reported RCTs comparing CDA with ACDF for the treatment of symptomatic cervical disc disease [ 25 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…The ectopic bone models previously developed (He and Xinghua 2006;Ganbat et al 2014) are appropriate for ectopic bone cases where mechanical stimuli are the main influence. It is accepted that osteophytes may form in response to the modified loading caused by degenerative changes in the vertebral discs.…”
Section: Resultsmentioning
confidence: 99%
“…The feedback can be considered as the error between some experienced stimulus and a steady state stimulus value. Previous authors have used a strain energy based modelling approach to model osteophytes (He and Xinghua 2006) and the development of ectopic bone formed after total disc replacement (Ganbat et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Ganbat et al . investigated HO formation after total disc replacement (TDR), and these studies were the first studies on HO formation using the bone adaptation process 18,19 . However, the ExGBF after ACDF has not been simulated, and its biomechanical effects on the operated spine have not been studied.…”
Section: Introductionmentioning
confidence: 99%